Penerapan Analisis Beban Berdasarkan SNI 1727:2020 untuk Meningkatkan Keamanan Struktural Balok pada Proyek Rumah Susun Kota Surakarta - Proklamalatu, Muhammad; Larasati, Atikah (Sustainable Civil Building Management and Engineering Journal, 2025)
The reconstruction of the Public Housing Project by the Government of Surakarta was initiated in response to structural failure in the previous building. Design modifications during the construction process—particularly in the beam elements—necessitated a reassessment of structural safety. This study aims to evaluate the safety of beams based on the Indonesian National Standard (SNI) 1727:2020, which regulates minimum load requirements for buildings. A quantitative descriptive method was employed using secondary data obtained from project documentation. The analysis focused on beam B45 as a representative sample, considering dead loads, live loads, and their respective combinations. The results indicate that the nominal moment capacity (Mn) of 326.72 kNm exceeds the ultimate moment (Mu) of 219.15 kNm, confirming that the beam is structurally safe under actual service loads. These findings underscore the importance of conducting technical evaluations for every design alteration to ensure continued compliance with safety standards.